New technique combining the Tone Reservation method with Clipping technique to reduce the Peak-to-Average Power Ratio - Hajar Abdelali (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Nonlinear distortions and impairments appear in multicarrier signal with high fluctuations when amplified by a Radio Frequency Power Amplifier (RF PA). Clipping (CL) technique offers a simple way to reduce these fluctuations in Orthogonal Frequency Division Multiplexing (OFDM) Technique, but may degrade seriously the transmission quality. This is why the new mobile standards propose other methods, like the Tone Reservation (TR) technique in the Digital Video Broadcasting-Terrestrial (DVB-T), that reduce the Peak-to-Average Power Ratio (PAPR) without reaching optimal performances. This paper deals with how we can use the TR technique, which exploits null sub-carriers for generating corrective signal, in combining to CL technique in order to improve PAPR reduction without data loss. Also, we show some comparison results on the PAPR reduction obtained with proposed scheme and other techniques. Experiments using a simulated example on a complete WiMax 802.16e transmitter have been made in order to investigate the PAPR reduction performances on presence of the non-linear Power Amplifier model based on gain compression response and phase distortion.